Harnessing cyclodextrins for enhanced ocular delivery of carotenoid derivatives: From development to ex vivo characterization - Réka Angi; Attila János Kalóczkai; Anna Kovács; András Marton; Vivien Bárdos; Péter Dormán; Gábor Katona; Attila Agócs; Anita Csorba; Zoltán Zs. Nagy; Anna Vincze; György T. Balogh (Carbohydrate Polymer Technologies and Applications)
Lutein and zeaxanthin, prominent carotenoids with antioxidant properties, contribute notably to maintaining of ocular health. These substances reduce the harmful effect of oxidative stress and blue light and ensure the vision quality. Carotenoids-rich dietary could have ophthalmic benefits, such as enhanced contrast perception and reduced eye fatigue, while also show potential in mitigating the risk of age-related macular degeneration (AMD). Nonetheless, ocular administration of carotenoids could enhance the local ophthalmic bioavailability of these compounds. The aim of this study was to investigate ophthalmic applicability of lutein (LutD) and zeaxanthin disuccinates (ZeaD) in aqueous solutions applying cyclodextrins to improve their solubility and permeability. Among the tested cyclodextrins, randomly methylated beta-cyclodextrin (RAMEB) was identified as the most effective solubilizing agent, achieving solubility values of 572±55 μM and 1470±103 μM for LutD and ZeaD, respectively. In vitro corneal-PAMPA and ex vivo porcine eye models demonstrated that RAMEB-based formulations significantly improved the permeability of both carotenoid derivatives by increasing their solubility (corneal concentration at 15 mins), markedly surpassing those of the reference suspensions. The findings suggest that RAMEB may be essential for developing carotenoid-based aqueous eye drops, leveraging its antioxidant properties to improve ocular health and ameliorate various degenerative eye conditions.